Black Men and ‘Pardo’ Militiamen in Piura during Cadiz Courts (1812-1813) - Espinoza Claudio, César (2017)
The Bourbons imposed a variety of transformations related to cultural differentiations and categories that were institutionalized in Piura’s province. There are few studies of these political changes in the early nineteenth century. In our 2013 and 2014 published papers, we verified that within this regional micro-space in northern coast of Peru’s viceroyalty there had been a redefinition of cultural boundaries between population groups that occupied the valleys of La Chira and Piura. On this occasion, we describe and analyze the performance of a ‘negro liberto’ (black freedman) in Sechura and also a page in the history of the ‘pardo’ militiamen (triple-breed, Amerindian/white/black men) confronted with liberal Creoles in Piura’s city during the early nineteenth century.